Penerapan Hukum terhadap Tindak Pidana Penyalahgunaan Narkotika di Wilayah Hukum Polres Pelabuhan Belawan - Herman Sentosa; Isnaini Isnaini; M. Citra Ramadhan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The purpose of this article is to analyze the legal arrangements, the application of the law and the obstacles to the application of the law against the crime of narcotics abuse in the Legal Area of the Belawan Port Police, the actions taken against narcotics addicts or abusers as a form of legal protection that should be based on science. A policy based on emotion, rhetoric, and without scientific evidence tends to be misleading. The research method used is descriptive method, while the data analysis technique uses qualitative. The results of the study show that legal arrangements regarding narcotics crimes according to Law no. 35 of 2009 concerning Narcotics is stated in article 54, as also stated in the RI Supreme Court Circular (SEMA) No. 04 of 2010. The handling of suspected narcotics abuse in the police is guided by Police Regulation No. 8 of 2021 concerning Handling of Crimes Based on Restorative Justice. The application of law to the criminal act of narcotics abuse in the Legal Area of the Belawan Port Police through legal substance, legal structure and legal culture. There are obstacles to law enforcement against narcotics abuse in the Legal Area of the Belawan Port Police, namely police regulations limiting the requirements for implementing restorative justice, relatively weak family economic conditions, difficulty differentiating suspected abusers and traffickers.